VALENCY-INCREASING MORPHOLOGICAL CATEGORIES IN TURKISH - Işıl AYDIN ÖZKAN (Fırat University, 2019)
Valency means logical, semantic and syntactic structural slot that a word creates in his surroundings. In accordance with mentioned word’s demand and requirement, this structural slot is completed with definite elements named actants that are located in phrase structure. The valency structure of a word can change because of a variety of reasons. The valency change means differentiation of valency frame of a word following semantic and morphological processes. Thus valency changing processes can be